Basic Bible prophecy - Rhodes, Ron (Eugene, Oregon : Harvest House Publishers, 2021)
"Primarily for curious newcomers, Basic Bible Prophecy is a straightforward breakdown of what you need to know about the future. Bestselling prophecy author Ron Rhodes provides a big-picture overview of the essential facts about Bible prophecy"--
How can we make sense of Bible prophecy? -- Who are the primary personalities of the end times? -- What are the primary elements of the end times? When do they occur? -- Where in the world will the end times prophecies unfold? -- Why does God give us prophecies of the end times?
Includes bibliographical references.
Adult
Keywords: Bible -- Prophecies; End of the world -- Biblical teaching